Patriotyzm w filozofii praktycznej Karola Libelta. Wokół rozprawy "O miłości ojczyzny" - Magdalena Woźniewska-Działak (Studia Philosophiae Christianae)
The 1840s was the time of an exceptionally lively debate on the identity of the Polish nation. Karol Libelt’s disquisition O miłości ojczyzny, published in the Poznań magazine Year in 1844, is one of the representative examples of the ideological ferment of this time. In his disquisition, the author formulates a fundamental question about the shape and character of the nation as a community of values. However, he redefines key concepts such as homeland and patriotism. He also postulates the need for a precise formulation of social roles and tasks, the implementation of which is aimed at regaining independence by Poland. Libelt emphasizes the issue of the inseparability of nation and state. Hence, questions about the subjectivity of the nation are closely related to the notion of a political being, which he examines with specific reference to its particular and universal mission in history. In the relatively rarely commented and underinvested research on Karol Libelt’s disquisition also echoes the need to change the structure of Polish society. Libelt, as the first Polish intellectual, formulated the definition of intelligentsia as a group of educated people with special competences and a key role to play in the self-seeking nation. On the shoulders of the intelligentsia, understood by the philosopher as the avant-garde of the nation, lies the responsibility to promote education in the country and attitudes that change its limiting-chances-of-possible-reforms worldview. Libelt defines the intellectual ethos as a set of values and principles with a pattern-making power. A special feature of the intellectual project of patriotism is the concept of serving the other person and making sacrifice for the good of the community, for the homeland. By the love of the fatherland he understands the attachment to the land, practicing customs, cultivating traditions, taking care of the beauty of the language, knowledge of national literature, respect for rights and civic duties, etc. The great value of Libelt’s disquisition is the combination of a historiosophical perspective with the ethos of group management, which results in a reflection of a sociological character, supported by a romantic moral maximalism.